2022
DOI: 10.3390/mi13030390
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of ZnO Piezoelectric Thin Film Sensors on GH4169 Superalloy Steel Substrate by Magnetron Sputtering

Abstract: At present, piezoelectric sensors are primarily applied in health monitoring areas. They may fall off owing to the adhesive’s durability, and even damage the monitored equipment. In this paper, a piezoelectric film sensor (PFS) based on a positive piezoelectric effect (PPE) is presented and a ZnO film is deposited on a GH4169 superalloy steel (GSS) substrate using magnetron sputtering. The microstructure and micrograph of ZnO piezoelectric thin films were analyzed by an X-ray diffractometer (XRD), energy dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…ZnO has a Zn 2+ ‐terminated, O 2− ‐terminated polar structure in which Zn atoms are arranged in the hexagonal closest stacking with four oxygen atoms around each Zn atom and further form a [ZnO 4 ] 6 tetrahedral coordination structure with one top angle of the tetrahedra pointing in the negative direction of the c ‐axis. As the XRD plots in Figure 1q show, under the predetermined process conditions, [ 40 ] all the prepared films showed intense ZnO(002) diffraction peaks at 2 θ of 34.17°, which were close to the standard card of PDF#36‐1451, indicating a good c‐axis orientation. A schematic of the ZnO crystal model is shown in Figure 1r.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…ZnO has a Zn 2+ ‐terminated, O 2− ‐terminated polar structure in which Zn atoms are arranged in the hexagonal closest stacking with four oxygen atoms around each Zn atom and further form a [ZnO 4 ] 6 tetrahedral coordination structure with one top angle of the tetrahedra pointing in the negative direction of the c ‐axis. As the XRD plots in Figure 1q show, under the predetermined process conditions, [ 40 ] all the prepared films showed intense ZnO(002) diffraction peaks at 2 θ of 34.17°, which were close to the standard card of PDF#36‐1451, indicating a good c‐axis orientation. A schematic of the ZnO crystal model is shown in Figure 1r.…”
Section: Methodsmentioning
confidence: 78%
“…The crosslinked conductive films not only need to have good conductivity without deformation but also need to have high conductivity and ductility while being well bonded to the substrate in various significant deformation situations. NiCr [40,41] is often used as a conductive electrode for flexible devices because of its chemical stability, good ductility, and electrical conductivity. After consideration, NiCr was used as the crosslinked conductive film.…”
Section: Experimental Section 21 Design Of Flexible Pressure Sensormentioning
confidence: 99%
“…The smart bolt used in this experiment is a double-layer piezoelectric layer structure that can enhance the piezoelectric performance of piezoelectric thin film sensors [43]. This method can reduce the measurement error caused by an adhesive, reduce the risk of falling off caused by adhesive aging, and ensure a better application in SHM [44]. Our laboratory has conducted SEM, EDS, and XRD characterization of ALN, NiSi, and SiO 2 thin films, and the results showed that the prepared thin films meet the preparation requirements of piezoelectric thin film sensors.…”
Section: Details Of Experimental Setupmentioning
confidence: 99%
“…In addition to its use in solar cells, zinc oxide has excellent piezoelectric properties and has been widely studied for use in piezoelectric sensors, nanogenerators, accelerometers, and pressure sensors. It can be deposited onto substrates using methods such as chemical vapor deposition, pulsed laser deposition, sol-gel treatment, and magnetron sputtering [4].…”
Section: Introductionmentioning
confidence: 99%